Korean Red ginseng extract inhibits glioblastoma propagation by blocking the Wnt signaling pathway. (23rd May 2019) - Ham, Seok Won; Kim, Jun-Kyum; Jeon, Hee-Young; Kim, Eun-Jung; Jin, Xiong; Eun, Kiyoung; Park, Cheol Gyu; Lee, Seon Yong; Seo, Sunyoung; Kim, Jung Yun; Choi, Sang-Hun; Hong, Nayoung; et al.
Abstract: Ethnopharmacological relevance: Korean Red ginseng extract (RG) is one of the most widely used traditional health functional food in Asia, which invigorates immunity and vital energy. RG have been suggested to inhibit proliferation, invasion, and inflammation in several cancer cell lines. Correspondingly, clinical studies have raised the possibility that RG could augment therapeutic efficacy in cancer patients. However, little is known about the anti-cancer effects of RG in glioblastoma (GBM), the most common and aggressive brain tumor for which effective therapeutic regimens need to be developed. Aim of this study: Here, we assessed the in vivo and in vitro anti-cancer properties of RG in a patient-derived xenograft mouse model and GBM stem cell (GSC) line. Materials and methods: We evaluated the anti-cancer effects of RG in patient-derived GBM xenograft mice with and without combined concurrent chemo- and radiation therapy (CCRT). Furthermore, we verified the in vitro effects of RG on the proliferation, cell death, and stem cell-like self-renewal capacity of cancer cells. Finally, we investigated the signaling pathway affected by RG, via which its anti-cancer effects were mediated. Results: When combined with CCRT, RG impeded GBM progression by reducing cancer cell proliferation and ionized calcium-binding adapter molecule 1 (IBA1)-positive immune cell recruitment. The anti-cancer effects of RG were mediated by Rg3 and Rh2 ginsenosides. Rg3 promoted cell death while Rh2 did not. Furthermore, both Rg3 and Rh2 reduced cell viability and self-renewal capacity of GSCs by inhibiting Wnt/β-catenin signaling. Conclusion: Therefore, our observations imply that RG could be applied to the GBM patients in parallel with CCRT to enhance therapeutic efficacy. Graphical abstract: Image 1